Representation of Existentialism in Jo Yong's Fairy Tales in the Drama It's Okay to Not Be Okay (A.J. Greimas Semiotic Analysis) - Syahrir, Hana Hanifah; Triarisanti, Risa; Widyana, Ashanti (QISTINA: Jurnal Multidisiplin Indonesia, 2024)
This research examines the fairy tale 진짜 진짜 얼굴을 찾아서 (Finding The Real Face) which is found in the Korean drama "It's Okay to Not Be Okay". This research analyzes the actant schema and functional structure from A.J.'s structural narrative theory. Greimas, after that, identified the representation of existentialism in it. The method used is qualitative with narrative semiotic analysis presented descriptively. The results of this research show that the fairy tale 진짜 진짜 얼굴을 찾아서 (Finding The Real Face) fulfills the six actants in varying amounts. The dominant actant of this tale is the Box Man, namely as subject, helper and recipient. The functional structure of a fairy tale has a sequential plot. Apart from that, this fairy tale reflects the search for identity of the characters, namely the Box Man, the Mask Child, and the Tin Can Princess.